Study of fossil forests with emphasis on fossil wood: fossilisation, analysis, pathology and conservation issues. The case study of the petrified forest in Ban Tak, Thailand - Κυριαζή, Ευαγγελία (Πανεπιστήμιο Πελοποννήσου, 2025)
The thesis is divided in three parts and it is completed with appendices. Part I is about the structure and composition of wood, the types and ways of fossilisation, fossiliferous sites and fossil forests, and the understanding and study of fossil wood and fossil forests. It presents the conservation challenges due to the different types of fossilisation, and the different pathologies that emerge by the in situ preservation of fossil forests to non-friendly to them environments. Part II is a case study for the petrified forest in Ban Tak, Thailand. In situ observations, photography and recording of pathology, testing for 3D laser scanning, record drawing, mapping, and satellite image processing are presented. Study of environmental parameters and laboratory examination of fossil and soil samples including documentation, macroscopic observation, soil classification, colorimetry, optical microscopy, scanning electron microscopy and statistical analysis, x-ray diffraction and gamma ray spectrometry were realised. The organisation of a conservation laboratory within the premises of the park, preliminary conservation tests and laboratory tests for the understanding of the fossils’ pathology, and actions for the sensitisation of the public are also presented. The last two chapters present conclusions on the burial environment, the nature of the fossils, their pathology, the effect of the environment, and conclusions and suggestions on their preservation and conservation. Part III sums suggestions on the protection, conservation and sustainable development of fossil forests, regardless of their type, pathology and geographic location, based on parts I-II of the thesis. It starts with suggestions for management and organisation, and founding of protected areas and geoparks. It continues with suggestions for sampling and analyses, techniques for the observation and recording of pathology, recording and processing of environmental data, and study of geological and geoenvironmental parameters. Advice for excavation, protective measures for excavation sites including disaster management and preventive conservation, a proposal for conservation ethics for in situ fossil forests, suggestions for conservation tests and conservation treatments, and ideas for the sensitisation of the public are given. Six appendices give additional information on the history of the study of fossil wood and analytical techniques employed in fossil forests, information on floral fossils other than wood, mineralogical terms useful for the description of petrified wood, and additional data and graphs of the climatological study and the analyses of the Ban Tak samples. The thesis is completed with an extensive bibliography.
Μελέτη απολιθωμένων δασών με έμφαση στο απολιθωμένο ξύλο: απολίθωση, ανάλυση, παθολογία και θέματα συντήρησης. Η μελέτη περίπτωσης του απολιθωμένου δάσους στο Ban Tak της Ταϊλάνδης
Keywords: Φασματοσκοπία Φθορισμού ακτίνων Χ στην αρχαιολογία; Αρχαιολογία -- Μεθοδολογία; Ξύλο -- Ανάλυση; Δέντρα, Απολιθώματα των -- Ανάλυση; Απολιθώματα -- Δείγματα τύπου; Παλαιοντολογία; Αρχαιομετρία; Προληπτική συντήρηση; Απολίθωση; Γεωπάρκα; Bantak Petrified Forest Park; XRD; SEM; Munsell; Fossils; Petrified forest; Palaeontological conservation; Paleontological conservation; Palaeontology; Paleontology; Archaeometry; Archeometry; Palaeometry; Paleometry; Optical microscopy; Fossil wood; Petrified wood; Environmental monitoring; Geoparks; Geopark; Scanning Electron Microscopy; Scanning electron microscopy; Gamma-ray spectrometry; Γ-ray spectrometry; Statistical analysis; Awareness rising; Fossilisation; Preventive conservation; Aπολιθώματα; Συντήρηση; Απολιθωμένο δάσος; Αρχαιομετρία; Παλαιομετρία; Οπτική μικροσκοπία; Απολιθωμένο ξύλο; Κλιματικά δεδομένα; Γεωπάρκο; Γεωπάρκα; Στατιστική ανάλυση; Προληπτική συντήρηση